Effect of biofouling roughness on a marine propeller's performance including cavitation and underwater radiated noise (URN). (February 2021) - Sezen, Savas; Uzun, Dogancan; Ozyurt, Refik; Turan, Osman; Atlar, Mehmet
Abstract: This study aims to investigate the effects of biofouling-related roughness on a propeller's hydrodynamic and underwater radiated noise (URN) performance. Selected benchmark INSEAN E779A propeller operated in uniform & open water flow under non-cavitating and cavitating conditions. The hydrodynamic flow field around the propeller was first solved using RANS (Reynolds-averaged Navier Stokes) solver. The Schnerr-Sauer cavitation model, based on reduced Rayleigh-Plesset equation, was used to model the sheet cavitation on the propeller blades and tip vortex cavitation (TVC) in the propeller's slipstream. A vorticity-based Adaptive Mesh Refinement (AMR) technique was employed for the observation of TVC. The porous form of the Ffowcs-Williams Hawkings (P-FWH) equation, which is coupled with the RANS solver, was used to predict the URN (or hydroacoustic performance) of the propeller. The propeller performance characteristics, including cavitation, were validated with the available experimental data. Following that, the roughness functions representing the different roughness configurations obtained from the literature were employed using wall function model of Computational Fluid Dynamics (CFD) solver. The results showed that roughness has detrimental impacts on the propeller's performance characteristics. That is to say that the propeller's thrust decreases while the torque increases with increasing severity of the roughness. Hence, the efficiency loss of the propeller at the most severe roughness condition can be as high as 30% and 25% at J = 0.795 and J = 0.71 & σ=1.763, respectively. Unlike its detrimental effects on the hydrodynamic performance, the roughness had some positive effects by reducing the cavitation volume, especially for the TVC and hence on the propeller underwater radiated noise (URN). The results also indicated that the URN levels might be reduced up to 10 dB between 1 kHz and 2 kHz. Besides, 2nd and 3rd BPF values decrease between 1 and 7 dB under varying roughness configurations in comparison to the smooth case. The study reported the effect of a particular biofouling roughness on the URN levels of a propeller for the first time in model-scale and using the CFD simulations.